2020
DOI: 10.1177/0885066620978729
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Following Pediatric Liver Transplant

Abstract: Objective: To determine the incidence, severity, and risk factors of postoperative acute kidney injury in pediatric liver transplant patients with and without inborn errors of metabolism. Design: Retrospective cohort study. Setting: Single-center PICU. Patients: All children less than or equal to 18 years old who received a liver transplant between January 2009 and July 2019. Interventions: None. Measurements and Main Results: Following exclusion criteria there were 92 transplant encounters. After excluding pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Although we performed intraoperative measurements of hourly UO in the pediatric recipients in our study, no statistically significant differences were found between them and post-LT AKI 9 . Arani et 17 pointed out that the level of sCr plays the most critical role in the occurrence of mild/moderate and severe AKI, which is consistent with the existing literature 11,24,25 . Haan et al 11 noted that impairment of preoperative renal function, either as CKD or AKI, could be a risk factor for post-LT AKI (26).…”
Section: Discussionsupporting
confidence: 81%
“…Although we performed intraoperative measurements of hourly UO in the pediatric recipients in our study, no statistically significant differences were found between them and post-LT AKI 9 . Arani et 17 pointed out that the level of sCr plays the most critical role in the occurrence of mild/moderate and severe AKI, which is consistent with the existing literature 11,24,25 . Haan et al 11 noted that impairment of preoperative renal function, either as CKD or AKI, could be a risk factor for post-LT AKI (26).…”
Section: Discussionsupporting
confidence: 81%
“…For example, our center employs strategies such as noninvasive monitoring of the fluid status, close monitoring of the tacrolimus levels, and critical inspection of drug administration by the clinical pharmacist in the PICU. In previous studies, factors associated with post-LT AKI in children included a history of AKI prior to transplantation [ 19 ], an elevated post-LT total bilirubin level, blood loss during surgery [ 20 ], a lower preoperative serum albumin level [ 23 ], and a prolonged international normalized ratio [ 21 ]. The authors postulated that the severity of preoperative synthetic liver function may be associated with the development of postoperative AKI [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, factors associated with post-LT AKI in children included a history of AKI prior to transplantation [ 19 ], an elevated post-LT total bilirubin level, blood loss during surgery [ 20 ], a lower preoperative serum albumin level [ 23 ], and a prolonged international normalized ratio [ 21 ]. The authors postulated that the severity of preoperative synthetic liver function may be associated with the development of postoperative AKI [ 21 ]. In this study, we found no association between AKI and the severity of liver disease as assessed by the PELD score.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Ferah et al [ 26 ] showed that the development of AKI was correlated with higher serum sodium and lower plasma albumin levels. In the post-liver transplant setting, the development of AKI represents a surrogate marker for the worst clinical course [ 24 , 26 ], what makes it important to detect potential early biomarkers for this evolution. Due to the retrospective nature of the study, however, it is possible only to establish correlations but not causality.…”
Section: Discussionmentioning
confidence: 99%